Comparative evaluation of instrumentation timing and cleaning efficacy in extracted primary molars using manual and NiTi rotary technique – Invitro study - Rachita Mehlawat; Rishabh Kapoor; Kapil Gandhi; Dipanshu Kumar; Ritika Malhotra; Shilpa Ahuja (Journal of Oral Biology and Craniofacial Research)
Aim: To compare the timing of instrumentation and cleaning efficacy between manual K files and NiTi rotary files in extracted primary molars. Study design: in-vitro study was conducted in 90 root canals of extracted primary molars which were subdivided in three groups viz. Control (No instrumentation), Manual (K files), Rotary (ProFiles) with 30 canals in each group. Mesiobuccal (MB) and Mesiolingual (ML) canals of mandibular molars, and MB and Distobuccal (DB) canals of maxillary molars were included in the test group whereas Distal canals in mandibular molars and Palatal canals in maxillary molars were included in the control group. Method: Teeth were mounted and canals were injected with India ink to stain the canal walls. Canal preparation was done as per the group. After instrumentation, teeth were demounted, decalcified and cleared to make them transparent for scoring according to the extent of removal of India ink. Timing of instrumentation and cleaning efficacy of canals in coronal, middle and apical thirds were assessed in each sample. Results: Mean timing of instrumentation in rotary group was 3.54 ± 1.14 min and 4.32 ± 1.04 min in manual group. Mean cleaning efficacy scores in manual and rotary groups were 2.03 and 1.66 in coronal third, 1.08 and 1.18 in middle third and 0.67 and 1.08 in apical third respectively. Inter-group comparisons showed no statistically significant difference in cleaning efficacy among test groups in all thirds of root canals. Conclusion: NiTi rotary technique has comparable cleaning efficacy, with significantly less timing of instrumentation compared to manual K-files.